1978
DOI: 10.1126/science.199.4332.973
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation and Delayed Leaf Senescence in Soybeans

Abstract: Delayed leaf senescence has been found in a soybean population which maintains its chlorophyll and ribulosebisphosphate carboxylase activity in leaves and nitrogen fixation (acetylene reduction) activity in root nodules throughout seed maturation. Incorporation of delayed leaf senescence into an agronomically desirable genetic background may help to increase seed yield and symbiotic nitrogen fixation during seed development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…This implies that higher nodulation required a larger amount of carbon and other nutrients to sustain nodule growth at the maturing stage. The nutritional unbalance may accelerate aging of the leaf resulting in lower photosynthetic activity (Abu-Shakra et al, 1978;Sinclair and de Wit 1975). To achieve the higher yielding by the crack fertilization technique, photosynthetic activity should be sustained at a later seed maturing stage, so that the competition between the nodule and seed does not occur at this stage.…”
Section: Biomass and Seed Production In The Fi Eld Experimentsmentioning
confidence: 99%
“…This implies that higher nodulation required a larger amount of carbon and other nutrients to sustain nodule growth at the maturing stage. The nutritional unbalance may accelerate aging of the leaf resulting in lower photosynthetic activity (Abu-Shakra et al, 1978;Sinclair and de Wit 1975). To achieve the higher yielding by the crack fertilization technique, photosynthetic activity should be sustained at a later seed maturing stage, so that the competition between the nodule and seed does not occur at this stage.…”
Section: Biomass and Seed Production In The Fi Eld Experimentsmentioning
confidence: 99%
“…This effect of population density could not be noted on the lower leaves of Enrei cultivar, but the spatial difference in rate of photosynthesis between the two types of leaves was similar to Shakujo. It has been reported that leaf carbon exchange capacity in soybean varies with time of origin, nodal position, developmental phase, genotypes, and environmental conditions (Dornhoff and Shibles, 1970;Abu-Shakra et al, 1978;Gordon et al, 1982;Egli, 1997). In our study, shading of the upper canopy layers and developmental stage might have impacted leaf photosynthesis of the older leaves on the lower units in both cultivars.…”
Section: Discussionmentioning
confidence: 63%
“…Soybeans, as well as most leguminous plants, possess the ability to acquire nitrogen for growth through nitrogen fixation and inorganic nitrogen uptake from the soil [14] [15]. Soybeans perform nitrogen fixation through its symbiotic association with Bradyrhizobioum japonicum bacteria [16] [17]. Bradyrhizobioum japonicum form nodules in soybean roots and facilitate the process of nitrogen fixation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Soybeans perform nitrogen fixation through its symbiotic association with Bradyrhizobioum japonicum bacteria [16] [17]. Bradyrhizobioum japonicum form nodules in soybean roots and facilitate the process of nitrogen fixation [16]. Nitrogen fixation is a biological phenomenon characterized by conversion of atmospheric molecular dinitrogen (N 2 ) to ammonium ion (…”
Section: Introductionmentioning
confidence: 99%